2021
DOI: 10.1002/pat.5491
|View full text |Cite
|
Sign up to set email alerts
|

Polyaniline decorated graphene oxide on sulfonated poly(ether ether ketone) membrane for direct methanol fuel cells application

Abstract: In direct methanol fuel cells (DMFC), methanol crossover is a major issue which has reduced the performance of polymer electrolyte membrane (PEM) for energy generation. In this study, graphene oxide (GO) and conductive polyaniline decorated GO (PANI-GO) were used as additives in fabrication of sulfonated poly(ether ether ketone) (SPEEK) nanocomposite PEM membrane to reduce methanol crossover. PANI-GO was synthesized by in situ polymerization method and the formation of PANI coated GO nanostructures was confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…45 reported that by adding polyaniline-coated graphene oxide to the SPEEK matrix, the glass transition of the SPEEK nanocomposite decreased. 46 A possible explanation for this might be that the introduced additive causes to the increase of fractional free volume in the matrix. 47 Another possible explanation for this is that when the interaction between filler and polymer matrix is repulsive such decrement in T g could be revealed, and it leads to the facilitation of the polymer chains mobility.…”
Section: Optimization Analysis Of Pcnt Diametermentioning
confidence: 99%
“…45 reported that by adding polyaniline-coated graphene oxide to the SPEEK matrix, the glass transition of the SPEEK nanocomposite decreased. 46 A possible explanation for this might be that the introduced additive causes to the increase of fractional free volume in the matrix. 47 Another possible explanation for this is that when the interaction between filler and polymer matrix is repulsive such decrement in T g could be revealed, and it leads to the facilitation of the polymer chains mobility.…”
Section: Optimization Analysis Of Pcnt Diametermentioning
confidence: 99%
“…The world is in the midst of an energy crisis due to the combination of dwindling fossil fuel supplies and rising energy use [1]. Fuel cells (FCs) are being studied as a possible tool for solving this issue.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, its barrier effect, modulated nanophase separation and decreased the void volume of the membrane by the interaction between GO and host polymers can increase the resistance of methanol crossover. ,, Therefore, it possesses grand promise for boosting proton conduction and restraining methanol permeation of PEMs. For example, sulfonated organosilane functionalized GO (SSi-GO)/SPEEK, sulfonated imidized GO (SIGO)/sulfonated poly­(imide) (SPI), sulfonated GO (SGO)/sulfonated CS (SCS)/CS, GO/sulfonated polyvinylidene fluoride (SPVDF), PA functionalized GO (PGO)/Nafion, polyaniline decorated GO (PANI-GO)/SPEEK, and phosphorous acid and sulfanilic acid modified GO (PS-MGO)/sulfonated polyethylene grafted polystyrene (PE-PS) composite PEMs were successfully fabricated. Improved proton conductivities and reduced methanol permeabilities were obtained for all of them.…”
Section: Introductionmentioning
confidence: 99%